Peculiar relationships among morphology, burrowing performance and sand type in two fossorial microteiid lizards - de Barros, Fábio C.; Grizante, Mariana B.; Zampieri, Felipe A.M.; Kohlsdorf, Tiana (Zoology (Jena), 2021)
•Patterns of phenotypic variation do not perfectly match optimization predictions of Ecomorphology.•We tested burrowing performance of two Calyptommatus lizards in different soil types.•In Calyptommatus lizards, expected associations among morphology-performance-habitat only emerge at the soil type that facilitates burying in the sand.•Manipulation of environmental conditions contributes to elucidate phenotypic evolution in fossorial lineages. Associations among ecology, morphology and locomotor performance have been intensively investigated in several vertebrate lineages. Knowledge on how phenotypes evolve in natural environments likely benefits from identification of circumstances that might expand current ecomorphological equations. In this study, we used two species of Calyptommatus lizards from Brazilian Caatingas to evaluate if specific soil properties favor burrowing performance. As a derived prediction, we expected that functional associations would be easily detectable at the sand condition that favors low-resistance burrowing. We collected two endemic lizards and soil samples in their respective localities, obtained morphological data and recorded performance of both species in different sand types. As a result, the two species burrowed faster at the fine and homogeneous sand, the only condition where we detected functional associations between morphology and locomotion. In this sand type, lizards from both Calyptommatus species that have higher trunks and more concave heads were the ones that burrowed faster, and these phenotypic traits did not morphologically discriminate the two Calyptommatus populations studied. We discuss that integrative approaches comprising manipulation of environmental conditions clearly contribute to elucidate processes underlying phenotypic evolution in fossorial lineages.